2008
DOI: 10.1007/s10811-008-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic carbon sources on growth, photosynthesis, and respiration of Phaeodactylum tricornutum

Abstract: The growth, photosynthesis, and respiration of the marine diatom Phaeodactylum tricornutum were examined under photoautotrophic and mixotrophic conditions. 100 mM glycerol, acetate, and glucose significantly increased specific growth rate, and mixotrophic growth achieved higher biomass concentrations. Under mixotrophic conditions, respiration rate (R d ) and light compensation irradiance (I c ) were significantly higher, but net maximum photosynthetic O 2 evolution rate (P m ) and saturation irradiance (I k ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 42 publications
(15 reference statements)
10
63
1
4
Order By: Relevance
“…Therefore, organic carbon sources reduced the photosynthetic efficiency in this phase, and the enhancement of biomass of A. platensis implied that organic sources had more pronounced effects on respiration than on photosynthesis. These conclusions are in agreement with results obtained with Phaeodactylum tricornutum under mixotrophic culture (Liu et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Therefore, organic carbon sources reduced the photosynthetic efficiency in this phase, and the enhancement of biomass of A. platensis implied that organic sources had more pronounced effects on respiration than on photosynthesis. These conclusions are in agreement with results obtained with Phaeodactylum tricornutum under mixotrophic culture (Liu et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Again, the other two microalgae showed no significant differences between their growth rates (around 0.85 d À1 ; p > 0.05), and biomass yields with maximum values (around 1.100 mg mL À1 ; p > 0.05) in late stationary phase (Table 1). Increase in growth parameters has been reported for cultures of P. tricornutum associated with mixotrophic growth and/or photobioreactors [20,21], as well as for N. oceanica cultured at different temperatures [22]. In contrast, growth rates and biomass yields for cultures of I. galbana reported in the literature are typically lower than those observed in the present work [23,24].…”
Section: Resultscontrasting
confidence: 44%
“…Therefore, organic carbon sources reduced the photosynthetic efficiency in this phase, and the enhancement of biomass of Arthrospira platensis implied that organic sources had more pronounced effects on respiration than on photosynthesis. These conclusions are in agreement with results obtained with Phaeodactylum tricornutum under mixotrophic culture (Liu et al, 2009). All the above results confirmed that, in the second phase, Arthrospira platensis might use and metabolize glucose and then shift to the heterotrophic nutrition mode.…”
Section: Experiments Factors Responsessupporting
confidence: 92%